Spatial Analysis of Residentials’ Uses and Future outlook in Qurna District - Oday Karim Baheya , Nada; Juma Ali, Prof.Dr.Tariq; Abdel Hassan Al-Eidani , Prof.Dr.Abaas (Basra studies journal, 2022)
The study of residential usage in Al Qurna district is of great importance because that the given area it occupies is about (590.4) hectares, which occupied (44.6%) of the total area which is about ​​(1322.5) hectares. The reason for the expansion of this area is due to the position of the city and its geographical characteristics and its administrative rank which made it a center of population attraction, the city’s population reached (137,648) according to estimates (2020), which required more spaces to build for housing units and to accommodate the population increase and facing pressure on land usage, including residential use. The study showed the real usage of Housing in the city of Qurna is not in line with the local planning standards and the size of the population.